IgG4‐related disease and lymphocyte‐variant hypereosinophilic syndrome: A comparative case series. (20th January 2017) - Carruthers, Mollie N.; Park, Sujin; Slack, Graham W.; Dalal, Bakul I.; Skinnider, Brian F.; Schaeffer, David F.; Dutz, Jan P.; Law, Joanna K.; Donnellan, Fergal; Marquez, Vladimir; Seidman, Michael; Wong, Patrick C.; et al.
Abstract: Objective: To compare the clinical and laboratory features of IgG4‐related disease (IgG4‐RD) and lymphocyte‐variant hypereosinophilic syndrome (L‐HES), two rare diseases that often present with lymphadenopathy, gastrointestinal symptoms, eosinophilia, and elevated immunoglobulins/IgE. Method: Comparative case series of 31 patients with IgG4‐RD and 13 patients with L‐HES. Results: Peripheral blood eosinophilia was present in eight of 31 patients with IgG4‐RD compared to 13 of 13 patients with L‐HES (median eosinophils 0.4 vs 7.0 giga/L, P =.001) and 12 of 20 patients with IgG4‐RD had increased serum IgE compared to eight of 13 patients with L‐HES, P =.930. Twenty‐seven of 30 patients with IgG4‐RD had elevated serum IgG4 compared to five of 12 patients with L‐HES (median IgG4 9.6 g/L vs 0.80 g/L, P =.002). Flow cytometry demonstrated an aberrant T‐cell phenotype in 7 of 23 patients with IgG4‐RD and 13 of 13 patients with L‐HES ( P <.001). T‐cell clonality by PCR was positive in 12 of 23 patients with IgG4‐RD vs 10 of 13 patients with L‐HES ( P =.143). Patients in both groups received corticosteroids as first‐line therapy. For refractory disease in IgG4‐RD, rituximab was the most common steroid‐sparing agent, whereas in L‐HES, it was pegylated interferon‐α‐2a. Conclusion: The overlapping features of these two diseases with divergent treatment options demonstrate the importance of familiarity with both entities to optimize diagnosis and treatment.